(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The increasing awareness of health and environmental sustainability has driven interest in organic vegetables. However, financial constraints remain a significant barrier to widespread adoption. This study examines consumer attitudes and unwillingness to pay (UWP) for organic vegetables in Samrala City, using Exploratory Factor Analysis (EFA) to identify key determinants influencing consumer behavior. Data were collected from 100 respondents through a structured questionnaire and analyzed. The results reveal two main factors: (1) Positive attitudes toward organic vegetables, driven by health benefits, environmental impact, and perceived taste; and (2) Unwillingness to pay, largely influenced by cost concerns, budget limitations, and price sensitivity.